2002
DOI: 10.1080/09540120220149957
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ancillary services on primary care use and outcomes for HIV/AIDS patients with public insurance coverage

Abstract: To better understand the impact of ancillary services on access to primary care, utilization of health services, costs and health status of HIV/AIDS patients, we studied adult HIV/AIDS patients eligible for public insurance for low-income people (Medicaid) in eastern North Carolina. Using primary data from a 1997 survey of such patients linked to Medicaid claims, multivariate logit analysis was used to estimate the effect of receiving housing, legal services and substance abuse treatment and of self-reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
1
26
1
Order By: Relevance
“…medical case management) for those who have co-occurring conditions that impact the effectiveness of HIV care [26,27]. Previous research in RWP-funded health clinics suggests receipt of care and support services in RWP-funded health clinics are associated with better engagement in care, retention in care and patient health outcomes [28][29][30][31][32]. However, these same findings also indicate that the improved engagement, retention and health outcomes are not yet at levels that would be considered ideal [30].…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…medical case management) for those who have co-occurring conditions that impact the effectiveness of HIV care [26,27]. Previous research in RWP-funded health clinics suggests receipt of care and support services in RWP-funded health clinics are associated with better engagement in care, retention in care and patient health outcomes [28][29][30][31][32]. However, these same findings also indicate that the improved engagement, retention and health outcomes are not yet at levels that would be considered ideal [30].…”
Section: Introductioncontrasting
confidence: 43%
“…Previous research in RWP-funded health clinics suggests receipt of care and support services in RWP-funded health clinics are associated with better engagement in care, retention in care and patient health outcomes [28][29][30][31][32]. However, these same findings also indicate that the improved engagement, retention and health outcomes are not yet at levels that would be considered ideal [30]. For example, only 45% of patients in RWP-funded clients reported any primary HIV care visits in the past year [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research demonstrated a clinical benefit from integrating social services and ancillary care with the medical model. [3][4][5][6][7][8][9][10] However, the findings suggest that the constellation of providers and agencies accessed in Baltimore are not keeping individuals out of emergency departments or from being admitted to the hospital. The significance of being the only city without a CAP grant, a program funded by the Health Resources and Services Administration that builds on existing capacity to help health providers develop integrated systems for the uninsured and underinsured, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Similarly, communitybased ancillary services provided in coordination with medical care have been shown in many studies to improve the care of patients with acquired immunodeficiency syndrome (AIDS). [5][6][7] Other working examples of this more inclusive model of safety net providers have been reported in maternal and child health care 8 and other areas. 9,10 How the safety net is defined is relevant to the current pressures for cost containment and more efficient utilization of services by poor and uninsured persons.…”
Section: Introductionmentioning
confidence: 99%